New Multidisciplinary Approaches for Reducing Food Waste in Agribusiness Supply Chains (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint is a collection of research articles that highlight the achievements of the team of the European project called the REAMIT, funded by Interreg North-West Europe and ERDF. The chapters of this reprint were published as articles in the Special Issue titled "New Multidisciplinary Approaches for Reducing Food Waste in Agribusiness Supply Chains" published in the journal Sustainability. We gratefully acknowledge the generous funding received from the Interreg North-West Europe for carrying out our activities. We believe that the reprint and individual chapters will be of interest to a wide and various audience and will kindle interests in food companies, technology companies, business support organisations, policy-makers and members of the academic community in finding ways to reduce food waste with and without the use of technology.